ENGLISH LANGUAGE LEARNING STRATEGY USED BY ULIL AL-BAAB NW GEGEK ISLAMIC BOARDING SCHOOL: A STUDY CASE - Mahrim Mahrim; Ahmad Zuhri Rosyidi (JURNAL ASIMILASI PENDIDIKAN, 2024)
Learning English in Indonesia is currently undergoing development due to the need for English that has covered the whole world. In improving the quality of English language education, the right strategy is needed in teaching the language. One of the Islamic boarding schools in East Lombok that is currently applying English as a daily language is ULIL AL-BAAB boarding school. This boarding school can be categorized as a successful school in implementing learning strategies for students. This research aims to look at the strategies used by Islamic boarding schools in improving students' language skills. This type of research is a case study whose data is taken through the process of observation and interview. The results of this study suggest that there are 3 strategies used by the school those peer teaching method, speaking club, and English area.